Effect of Immobilizing Bacillus megaterium on the Compressive Strength and Water Absorption of Mortar - David Munyao Musyoki; Jackson Wachira Muthengia; Joanne Ogunah; Daniel Karanja Mutitu; John Kinuthia; Romano Mwirichia; Joseph Karanja Thiong’o; Munyao Onesmus Mulwa; Murithi Genson (Journal of Chemistry)
The world’s growing population and industrialization have led to increased construction activities. This has increased the amount of waste aggregates which can be recycled in construction and cut the cost of infrastructure development. This study, therefore, reports the experimental findings for the effect of immobilizing Bacillus megaterium on the compressive strength and water absorption of laboratory prepared test mortar. Bacterial solution used in this work had a concentration of 1.0 × 107 cells/mL. The impact of recycled mortar impregnated with bacteria was studied after curing the specimens in water, saturated lime water, and 1.5% sulfuric acid. Compressive strength for test specimens cured in the three media was determined at the 2nd, 7th, 28th, and 56th day of curing. SEM analysis was done for mortars cured in acidic media and saturated lime water after curing for 28 days. The test results indicated that curing in water and saturated water improved the compressive strength, while the acidic medium lowered it. Recycled mortar is, therefore, an ideal material for immobilizing Bacillus megaterium before introduction into fresh concrete/mortar. The use of recycled mortar is a good strategy to reduce wastes from construction activities, save on the cost of construction materials, and enhance environmental conservation.